Penerapan Metode Prototype dalam Pengembangan Sistem Informasi Inventory Barang Berbasis Web - Aprilisa, Shinta; Aulia, Rizka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
An inventory information system is a system used to determine the stock of goods in a place or company. CV. Multikom is a company that operates in the field of computer equipment. In this company there are problems that occur in the current system, namely the processing of incoming and outgoing goods data, goods delivery data, and customer data that has not been integrated, as well as travel document data collection which is done only on a piece of paper and then copied to the computer by the warehouse admin, so that those who experience difficulties with the goods, the information provided is in accordance with the existing goods. The aim of this research is to design a Goods Inventory Information System to make it easier to collect data on incoming and outgoing goods, stock of goods, customer data, shipping, order transactions using the Prototype method and using Data Flow Diagrams (DFD) for structured modeling.